Cannabis as medicine - Wedman-St. Louis, Betty (Boca Raton : CRC Press, 2019)
For hundreds of years cannabis has been used as a therapeutic medicine around the world. Cannabis was an accepted medicine during the second half of the 19th century, but its use declined because single agent pain medications were advocated by physicians who demanded standardization of medicines. It was not until 1964 when the chemical structure of THC (delta 9-tetrahydrocannabinol) was elucidated and its pharmacological effects began to be understood. Numerous therapeutic effects of cannabis have been reviewed, but cannabis-based medicines are still an enigma because of legal issues. Many patients could benefit from cannabinoids, terpenoids and flavonoids found in Cannabis sativa L. These patients suffer from medical conditions including chronic pain, chronic inflammatory diseases, neurological disorders, and other debilitating illnesses. As more states are legalizing medical cannabis, prescribers need a reliable source which provides clinical information in a succinct format. This book focuses on the science of cannabis as an antioxidant and anti-inflammatory supplement. It discusses cannabis uses in the human body for bone health/osteoporosis; brain injury and trauma; cancer; diabetes; gastrointestinal conditions; mental health disorders; insomnia; pain; anxiety disorders; depression; migraines; eye disorders; and arthritis and inflammation. There is emphasis on using the whole plant from root to raw leaves and flowers discussing strains, extraction and analysis, and use of cannabis-infused edibles. Features: Provides an understanding of the botanical and biochemistry behind cannabis as well as its use as a dietary supplement. Discusses endocannabinoid system and cannabinoid receptors. Includes information on antioxidant benefits, pain receptors using cannabinoids, and dosage guidelines. Presents research on cannabis treatment plans, drug-cannabis interactions and dosing issues, cannabis vapes, edibles, creams, and suppositories. Multiple appendices including a glossary of cannabis vocabulary, how to use cannabis products, a patient guide and recipes as well as information on cannabis for pets.
OCLC-licensed vendor bibliographic record.
Keywords: Cannabis -- Therapeutic use; MEDICAL / Alternative Medicine; MEDICAL / Nutrition; MEDICAL / Public Health